2014
DOI: 10.1039/c4dt02133a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and analysis of the anticancer activity of platinum(ii) complexes incorporating dipyridoquinoxaline variants

Abstract: Eight platinum(II) complexes with anticancer potential have been synthesised and characterised. These complexes are of the type [, where I L is either dipyrido[3,2-f:2',3'-h]quinoxaline (dpq) or 2,3-dimethyl-dpq (23Me 2 dpq) and A L is one of the R,R or S,S isomers of either 1,2-diaminocyclohexane (SS-dach or RR-dach) or 1,2-diaminocyclopentane (SS-dacp or RR-dacp). The CT-DNA binding of these complexes and a series of other complexes were assessed using fluorescent intercalator displacement assays, resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
29
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 49 publications
(94 reference statements)
11
29
1
1
Order By: Relevance
“…Complexes such as the aforementioned [Pt(phen)(en)] 2+ (10) intercalate into the minor groove of DNA predominantly between the base pairs C 3 -G 4 and T 2 -A 5, and as a result the helix is lengthened and rigidified (Fig. 112,[115][116][117] For example, methyl substituents in the 5/6 position of phen is known to be particularly effective, with some complexes achieving cytotoxicity at nanomolar concentrations. 63 The positive charge of these complexes allows for improved solubility, selective cellular uptake via active transport and high DNA affinity.…”
Section: Intercalationmentioning
confidence: 99%
See 1 more Smart Citation
“…Complexes such as the aforementioned [Pt(phen)(en)] 2+ (10) intercalate into the minor groove of DNA predominantly between the base pairs C 3 -G 4 and T 2 -A 5, and as a result the helix is lengthened and rigidified (Fig. 112,[115][116][117] For example, methyl substituents in the 5/6 position of phen is known to be particularly effective, with some complexes achieving cytotoxicity at nanomolar concentrations. 63 The positive charge of these complexes allows for improved solubility, selective cellular uptake via active transport and high DNA affinity.…”
Section: Intercalationmentioning
confidence: 99%
“…63 The positive charge of these complexes allows for improved solubility, selective cellular uptake via active transport and high DNA affinity. 112 The A L s of these complexes greatly influence their activity, 101,110 which suggests that their cytotoxicity is not just a consequence of DNA binding, but of additional intracellular interactions also. 112,[115][116][117] For example, methyl substituents in the 5/6 position of phen is known to be particularly effective, with some complexes achieving cytotoxicity at nanomolar concentrations.…”
Section: Intercalationmentioning
confidence: 99%
“…These compounds are of the type [Pt(P L )(A L )] 2+ , in which P L is a substituted 1,10‐phenanthroline (phen) polyaromatic ligand and A L is a chiral amine ancillary ligand such as 1 S ,2 S ‐diaminocyclohexane 5. Recently we have also reported that complexes of dipyrido[3,2‐ f :2′,3′‐ h ]quinoxaline (dpq) and 2,3‐dimethyl‐dpq (23Me 2 dpq) exhibit biological activity comparable to complexes with phen derivatives 6. Here we present an expansion of the range of P L s via a study of complexes of 2,2′‐bipyridine (bpy), 4,4′‐dimethyl‐bpy (44Me 2 bpy) and 2‐(2′‐pyridyl)quinoxaline (2pq), with either 1 S ,2 S ‐diaminocyclohexane ( SS ‐dach) or 1 R ,2 R ‐diaminocyclohexane ( RR ‐dach) as an A L (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast intercalators have received less attention; however, there are several recent examples of platinum intercalators that exhibit exceptionally high anticancer activity. A prominent series of complexes are composed of a general scaffold of [Pt(H L )(A L )] 2+ , where H L is a heterocyclic intercalating ligand and A L is a bidentate ancillary ligand [25,26]. These complexes include dipyrido[3,2- f :2’,3’- h ]quinoxaline (dpq), 2,3-dimethyl-dpq (23Me 2 dpq), phen, 5,6-dimethyl-phen (56Me 2 phen), bpy or 4,4’-dimethyl-bpy (44Me 2 bpy) as the H L and either the S , S or R , R isomer of 1,2-diaminocyclohexane ( S , S - or R , R -dach) as the A L (Figure 4).…”
Section: Platinummentioning
confidence: 99%
“…However, DNA affinity is not the only factor governing the activity of these complexes as the choice of A L has a large effect. For example, complexes of S , S -dach (i.e., Pt1 and Pt3 ) displayed higher cytotoxicity than those of R , R -dach (i.e., Pt1’ and Pt3’ ), despite exhibiting the same DNA affinity [25]. …”
Section: Platinummentioning
confidence: 99%